2020
DOI: 10.3758/s13414-020-02184-y
|View full text |Cite
|
Sign up to set email alerts
|

Attention extends beyond single words in beginning readers

Abstract: A common notion is that during the first stages of learning to read, attention is narrowly focused so as to encompass only a single or a few letters. In skilled adult readers, however, attention extends beyond single words. The latter is evidenced by faster recognition of words that have many letters in common with surrounding words, along with correlations between such integration effects and measures of attention. These premises suggest that the distribution of attention gradually increases as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Specifically, reduced between-items spacing is known to impede target recognition (e.g., Eriksen & Eriksen, 1974; Moll & Jones, 2013; Perea & Gomez, 2012; Rayner et al, 1998, 2013; Sheridan et al, 2013). With respect to naming direction, parafoveal processing for linguistic material is known to occur to a larger extent in the default reading direction of the language (e.g., Snell et al, 2018, 2021; Snell & Grainger, 2018). The perceptual span of parafoveal processing is shorter in the vertical direction, if the default reading direction is left-to-right (e.g., Ojanpää et al, 2002; Seo & Lee, 2002; Snell et al, 2018), and it can be extended toward the opposite direction for nonlinguistic material (i.e., left-oriented for readers of a left-to-right orthography; e.g., Harms & Bundesen, 1983).…”
Section: Conflict Monitoring and Expected Value Of Controlmentioning
confidence: 99%
“…Specifically, reduced between-items spacing is known to impede target recognition (e.g., Eriksen & Eriksen, 1974; Moll & Jones, 2013; Perea & Gomez, 2012; Rayner et al, 1998, 2013; Sheridan et al, 2013). With respect to naming direction, parafoveal processing for linguistic material is known to occur to a larger extent in the default reading direction of the language (e.g., Snell et al, 2018, 2021; Snell & Grainger, 2018). The perceptual span of parafoveal processing is shorter in the vertical direction, if the default reading direction is left-to-right (e.g., Ojanpää et al, 2002; Seo & Lee, 2002; Snell et al, 2018), and it can be extended toward the opposite direction for nonlinguistic material (i.e., left-oriented for readers of a left-to-right orthography; e.g., Harms & Bundesen, 1983).…”
Section: Conflict Monitoring and Expected Value Of Controlmentioning
confidence: 99%
“…Specifically, reduced between-item spacing is known to impede target recognition (e.g., Eriksen & Eriksen, 1974;Moll & Jones., 2013;Perea & Gomez, 2012;Rayner et al, 1998;Rayner et al, 2013;Sheridan et al, 2013). With respect to naming direction, parafoveal processing for linguistic material is known to occur to a larger extent in the default reading direction of the language (e.g., Snell, Mathôt et al, 2018;Snell et al, 2021). The perceptual span of parafoveal processing is shorter in the vertical direction, if the default reading direction is left-toright (e.g, Ojanpää et al, 2002;Seo & Lee, 2002;, and it can be extended toward the opposite direction for non-linguistic material (i.e., left-oriented for readers of a left-to-right orthography; e.g., Harms & Bundesen, 1983).…”
Section: Hypothesis 2: the Multi-item Stroop Task Is A Multi-taskmentioning
confidence: 99%
“…In these studies, the observed parafoveal-onfoveal effects (POF effects), i.e., the influence of parafoveal words on the processing of foveal words, were generally considered as evidence of parallel word processing (Kennedy and Pynte, 2005;Zang et al, 2023), although some researchers have argued that POF effects could also be accounted for by mislocated fixations (Drieghe et al, 2008;Drieghe, 2011). The other category employed visual word recognition tasks (e.g., Dare and Shillcock, 2013;Snell et al, 2017aSnell et al, ,b, 2019Snell et al, , 2021White et al, 2018White et al, , 2019bWhite et al, , 2020Cauchi et al, 2020;Kobayashi and Ogawa, 2020;Meade et al, 2021). Among these tasks, the flankers task has been employed quite widely (e.g., Dare and Shillcock, 2013;Grainger et al, 2014;Snell et al, 2017cSnell et al, , 2021Kobayashi and Ogawa, 2020;Meade et al, 2021. In the classic flankers task, participants were presented with a foveal target stimulus (e.g., a letter or a number) surrounded by flanking stimuli and were asked to respond to the target while disregarding the flankers (Eriksen et al, 1973;Eriksen and Eriksen, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…The other category employed visual word recognition tasks (e.g., Dare and Shillcock, 2013;Snell et al, 2017aSnell et al, ,b, 2019Snell et al, , 2021White et al, 2018White et al, , 2019bWhite et al, , 2020Cauchi et al, 2020;Kobayashi and Ogawa, 2020;Meade et al, 2021). Among these tasks, the flankers task has been employed quite widely (e.g., Dare and Shillcock, 2013;Grainger et al, 2014;Snell et al, 2017cSnell et al, , 2021Kobayashi and Ogawa, 2020;Meade et al, 2021. In the classic flankers task, participants were presented with a foveal target stimulus (e.g., a letter or a number) surrounded by flanking stimuli and were asked to respond to the target while disregarding the flankers (Eriksen et al, 1973;Eriksen and Eriksen, 1974). In the flankers task used to investigate parallel word processing, the foveal target word and the parafoveal flankers were simultaneously exposed for approximately 150 ms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation